Demographic Changes and Economic Growth in Pakistan: The Role of Capital Stock (The Pakistan Development Review, 2020)
Pakistan has experienced a decrease in population growth since the early 1990s leading to an increase in the ratio of working age population, known as demographic dividend. The demographic dividend may lead to higher savings and investments, which spurs economic growth. Given this postulation, the study is the first of its kind to analyse the impact of demographic variables on economic growth through physical capital for Pakistan from 1960 to 2014. In this regard, the demographic change is captured by taking four alternate measures, namely population growth, young age dependency ratio, old age dependency ratio and working age population ratio. In order to examine the channel effect, first the direct impact of demographic changes on physical capital is estimated. Later, the impact of demographically induced capital stock on economic growth is estimated. By using the FMOLS technique, the study concludes that the total negative impact is highest in the case of old age dependency, which means that higher old age dependency is the most threatening demographic change for economic growth. The least harmful demographic change is young age dependency. Moreover, the empirical findings highlight the importance of capital stock as the mediating channel in the demographic change and economic growth relationship. The study recommends effective long- term policies to increase youth employment and to enhance savings for maximising the benefits of demographic dividend. JEL Classification: J11; O47 Keywords: Direct and Indirect Impact, Demographic Transition, Demographic Age Structure, Capital Stock, FMOLS